1987
DOI: 10.1097/00000658-198708000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cholecystokinin and Pancreatic Polypeptide Response after Radical Pancreatoduodenectomy with Billroth I and Billroth II Type of Reconstruction

Abstract: This study was conducted to elucidate plasma cholecystokinin (CCK) and pancreatic polypeptide (PP) response after pancreatoduodenectomy and to compare response of CCK and PP in patients who had pancreatoduodenectomy with Billroth I and Billroth II type of reconstruction. Basal levels of plasma CCK were significantly lower in patients who had pancreatoduodenectomy (9.6 +/- 0.8 pmol/L) than in the control (preoperative patients: 14.6 +/- 2.0 pmol/L) probably because of the removal of the entire duodenum due to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…1987;Malfertheiner et al, 1987: Rieu et al. 1990 CCK response is in line with other reports both in man and the rat (Hopman et al, 1984;Inoue et al. 1987: Malfertheiner et al.…”
Section: Experimental Designsupporting
confidence: 82%
See 1 more Smart Citation
“…1987;Malfertheiner et al, 1987: Rieu et al. 1990 CCK response is in line with other reports both in man and the rat (Hopman et al, 1984;Inoue et al. 1987: Malfertheiner et al.…”
Section: Experimental Designsupporting
confidence: 82%
“…Although partial gastrectomy does not increase fasting levels of CCK in man or the rat, the CCK response to ingested fat is markedly greater in both species (Hopman et al. 1984;Inoue et al. 1987;Malfertheiner et al.…”
mentioning
confidence: 99%
“…Even the elderly can be operated on with comparable outcome [15][16]. A Bill roth-1-type reconstruction as used in the present series, with the biliary anastomosis in the natural position 4-5 cm distal to the duodenojejunal anastomosis, was first described by Watson [17], The excellent functional and physiological results of this method of restoration of gas trointestinal continuity after pancreaticoduodenectomy have been confirmed by others [18][19][20].…”
Section: Discussionmentioning
confidence: 55%
“…To explore the cause of this dichotomy in hepatic and peripheral insulin sensitivity, the role of pancreatic polypeptide (PP) was considered, as PP deficiency had also been documented in CP [31], pancreatic resection [32] and cystic fibrosis [33]. Bastidas et al [34] were unable to show any effect of acute administration of bovine PP on glucose metabolism and insulin action in an animal model of CP; however, Sun et al [26] found that the prolonged administration of PP for hours or days resulted in a reversal of the hepatic resistance to insulin in dogs with CP.…”
Section: Pancreatogenic Diabetesmentioning
confidence: 99%